Juridical Review of Agreements Using Adhesion Clauses in Lease Contracts: Uji Keabsahan Perjanjian yang Menggunakan Klausul Adhesion dalam Kontrak Sewa - Abdur Rozaq Setiawan; Noor Fatimah Mediawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Standard form contracts are widely used in service industries, including vehicle rental, to streamline transactions and reduce administrative burdens. Specific Background: In car rental practices, these contracts frequently contain adhesion clauses drafted unilaterally by business operators, potentially creating disparities in rights and obligations between providers and consumers. Knowledge Gap: Previous legal studies have largely addressed contractual justice in general terms, leaving limited empirical examination of how adhesion clauses operate in actual car rental agreements and how they relate to consumer protection norms. Aims: This study analyzes the juridical implications of adhesion clauses in a car rental contract in Tanggulangin, Sidoarjo, focusing on contractual balance, legal compliance, and consumer rights. Results: Using a normative-empirical approach supported by document analysis and interviews, the study finds that several clauses transfer risks disproportionately to consumers, impose strict penalties without flexibility, require extensive personal guarantees, and conflict with statutory consumer protection provisions and principles of good faith. Novelty: The research provides a direct field-based evaluation of specific contractual provisions, highlighting structural inequalities embedded in real operational practices rather than theoretical models. Implications: The findings underscore the necessity for regulatory reform, standardized contract drafting, and stronger oversight to ensure fairness, transparency, and legal certainty in consumer transactions within the vehicle rental sector. Highlights: Several provisions shift liability almost entirely to renters, including circumstances involving service staff. Penalty schemes operate rigidly without accommodating emergency situations. Personal document guarantees create legal and privacy concerns for users. Keywords:Adhesion Clause; Car Rental Agreement; Consumer Protection Law; Standard Contract; Contractual Balance